Teaching Systematic Searching Methods to Public Health Graduate Students: Repeated Library Instruction Sessions Correlate With Better Assignment Scores - Pell, John (Evidence Based Library and Information Practice, 2017)
Objective – The objective of this study was to devise an assessment plan to determine if repeat attendance at two library instruction sessions is statistically associated with overall assignment scores or specific assignment qualities.Methods – The author used SPSS to calculate correlations between attendance and assignment scores and cross tabulations between attendance and assignment item analysis scores.Results – Repeat attendance at two library instruction sessions was statistically associated with higher overall assignment scores and higher scores on specific assignment sections. The effect is statistically significant.Conclusion – Students who attended two library instruction sessions applied skills and concepts practiced in those sessions on a subsequent research assignment. Not all skills and concepts practiced in the session were applied. Acquisition of more technical skills such as Boolean searching may require a greater number of follow-up sessions.